Hot corrosion behaviour of carbon nanotubes reinforced chromium oxide composite coatings at elevated temperature. (12th September 2018) - Goyal, Khushdeep; Singh, Hazoor; Bhatia, Rakesh
Abstract: The present work aims to investigate the hot corrosion resistance of HVOF (high velocity oxy fuel) sprayed CNT (Carbon nanotubes) reinforced Cr2 O3 coated ASTM-SA213-T22 (T22) steel at 800 °C temperature in molten salt environment. The coatings have been deposited with high velocity oxy fuel process. The samples were exposed to hot corrosion in a Silicon tube furnace at 800 °C for 50 cycles. The kinetics of corrosion behaviour were analysed by the weight gain measurements after each cycle. Corrosion products were analysed with x-ray diffraction, scanning electron microscopy, energy dispersive and x-ray analysis techniques. During investigations, the CNT reinforced Cr2 O3 composite coatings on T22 steel were found to provide better corrosion resistance in the molten salt environment at 800 °C. The coatings showed lower weight gain along with formation of protective oxide scales during the experiment. Improvement in protection against hot corrosion was observed with increase in CNT content in the coating matrix. The addition of CNT has resulted in reduction in porosity by filling the voids in chromium oxide coating, with interlocking of particle and has blocked the penetration of corroding species to enhance the corrosion resistance of the composite coatings. The corrosion rate was found to be decreasing with increase in CNT content in coating matrix.